Development of co-dominant KASP markers co-segregating with Ug99 effective stem rust resistance gene Sr26 in wheat - Qureshi, N.; Pakeerathan, K.; Gessese, M.K.; Nsabiyera, V. (Mol Breeding, 2018)
Stem rust of wheat, caused by Puccinia graminis f. sp. tritici (Pgt), is a threat to global food security due to its ability to cause total crop failures. The Pgt race TTKSK (Ug99) and its derivatives detected in East Africa carry virulence for many resistance genes present in modern cultivars. However, stem rust resistance gene Sr26 remains effective to all races of Pgt worldwide. Sr26 is carried on the Agropyron elongatum (syn. Thinopyrum ponticum) segment 6Ae#1L translocated to chromosome 6AL of wheat. In this study, a recombinant inbred line (RIL) population derived from a cross between the landrace Aus27969 and Avocet S, which carries Sr26, was used to develop co-dominant kompetitive allele-specific polymerase chain reaction (KASP) markers that co-segregate with Sr26. Four KASP markers (sunKASP_216, sunKASP_218, sunKASP_224 and sunKASP_225) were also shown to co-segregate with Sr26 in four additional RIL populations. When tested on Australian cultivars and breeding lines, these markers amplified alleles alternate to that linked with Sr26 in all cultivars known to lack this gene and Sr26-linked alleles in cultivars and genotypes known to carry Sr26. Genotypes WA-1 and WA-1/3*Yitpi carrying the shortest Sr26 translocation segment were positive only for markers sunKASP_224 and sunKASP_225. Our results suggest the four KASP markers are located on the original translocation and sunKASP_224 and sunKASP_225 are located on the shortened version. Therefore, sunKASP_224 and sunKASP_225 can be used for marker-assisted pyramiding of Sr26 with other stem rust resistance genes to achieve durable resistance in wheat.
Keywords: Puccinia graminis; Marker-assisted breeding